Impact of Mothers’ Schistosomiasis Status During Gestation on Children’s IgG Antibody Responses to Routine Vaccines 2 Years Later and Anti-Schistosome and Anti-Malarial Responses by Neonates in Western Kenya - Ondigo, Bartholomew N.; Muok, Erick M. O.; Oguso, John K.; Njenga, Sammy M.; Kanyi, Henry M.; Ndombi, Eric M.; Priest, Jeffrey W.; Kittur, Nupur; Secor, William Evan; Karanja, Diana M. S.; Colley, Daniel G. (Frontiers in Immunology, 2018)
The potential consequences of parasitic infections on a person’s immune responsiveness to unrelated antigens are often conjectured upon in relationship to allergic responses and autoimmune diseases. These considerations sometimes extend to whether parasitic infection of pregnant women can influence the outcomes of responses by their offspring to the immunizations administered during national Expanded Programs of Immunization (EPI). To provide additional data to these discussions, we have enrolled 99 close-to-term pregnant women in western Kenya and determined their Schistosoma mansoni and Plasmodium falciparum infection status. At 2 years of age, when the initial immunization schedule was complete, we determined their children’s IgG antibody levels to tetanus toxoid, diphtheria toxoid, and measles nucleoprotein (N-protein) antigens using a multiplex assay. We also monitored antibody responses during the children’s first 2 years of life to Plasmodium falciparum MSP119 (PfMSP119), S. mansoni Soluble Egg Antigen (SEA), Ascaris suum hemoglobin (AsHb), and Strongyloides stercoralis (SsNIE). Mothers’ infections with either P. falciparum or S. mansoni had no impact on the level of antibody responses of their offspring or the proportion of offspring that developed protective levels of antibodies to either tetanus or diphtheria antigens at 2 years of age. However, children born of S. mansoni-positive mothers and immunized for measles at 9 months of age had significantly lower levels of anti-measles N-protein antibodies when they were 2 years old (p = 0.007) and a lower proportion of these children (62.5% vs. 90.2%, OR = 0.18, 95% CI = 0.04 to 0.68, p = 0.011) were considered positive for measles N-protein antibodies. Decreased levels of measles antibodies may render these children more susceptible to measles infection than children whose mothers did not have schistosomiasis. None of the children demonstrated responses to AsHb or SsNIE during the study period. Anti-SEA and anti-PfMSP119 responses suggested that 6% and 70% of the children acquired schistosomes and falciparum malaria, respectively, during the first 2 years of life.